1997
DOI: 10.1136/fn.77.1.f23
|View full text |Cite
|
Sign up to set email alerts
|

Doppler assessment of pulmonary artery pressure in neonates at risk of chronic lung disease

Abstract: Aim-To evaluate the pulmonary artery pressure (PAP) change in very low birthweight (VLBW) infants at risk of chronic lung disease (CLD). Methods-The time to peak velocity:right ventricular ejection time (TPV:RVET) ratio calculated from the pulmonary artery Doppler waveform, which is inversely related to PAP, was used. The TPV:RVET ratio was corrected for diVerent heart rate (TPV:RVET(c)). Seventy three VLBW infants studied on days 1, 2, 3, 7, 14, 21 and 28 were enrolled for the analysis. Results-Twenty two inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
11
1
3
Order By: Relevance
“…Vascular abnormalities associated with BPD may lead to pulmonary arterial hypertension. 23 We and others have shown that iNO may be used safely in neonates for prevention 27 or treatment of BPD. 24,36 Nitric oxide does not have any adverse effects on surfactant, 37 but evidence for iNO efficacy remains insufficient to recommend its use for BPD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Vascular abnormalities associated with BPD may lead to pulmonary arterial hypertension. 23 We and others have shown that iNO may be used safely in neonates for prevention 27 or treatment of BPD. 24,36 Nitric oxide does not have any adverse effects on surfactant, 37 but evidence for iNO efficacy remains insufficient to recommend its use for BPD.…”
Section: Discussionmentioning
confidence: 97%
“…right ventricular ejection time. [23][24][25] To treat associated pulmonary hypertension, 10 ppm inhaled nitric oxide (iNO) were added for 1 to 3 weeks, depending on weekly hemodynamics evaluations.…”
Section: Key Pointsmentioning
confidence: 99%
“…A value >40 mm Hg was considered as pulmonary hypertension. 22,23 Doppler echocardiography was only performed at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…SVC flow, Doppler measurement of right ventricular output (RVO), left pulmonary artery velocity, colour Doppler diameter of ductus arteriosus shunt and size, and Doppler of the middle cerebral arteries (MCAs) were performed according to previously published methods 9 10. Doppler assessment of pulmonary artery pressure was also performed using the time to peak velocity divided by the right ventricular ejection time (TPV/RVET) 11. All measurements were performed by one investigator (KW).…”
Section: Methodsmentioning
confidence: 99%